Dose assessment from exposure to uranium and radon in groundwater in Safi province, Morocco. - Samyh, Bouchra; Nachab, Abdellatif; Jabbade, Meryame; Nourreddine, Abdel-Mjid (International Journal of Environmental Health Research, 2025)
In this study we evaluate the uranium and radon concentrations in groundwater from the Province of Safi. The samples were collected from 58 wells across five communes and analyzed using the LR-115 type II detector. Results indicate that uranium concentrations ranged from the Limit of Detection (LLD) to 3.73 µg/l, with a mean of 0.72 µg/l, well below the World Health Organization's safe limit of 30 µg/l. Radon levels varied from LLD to 2.39 Bq/l, with an average of 0.60 Bq/l, also below the United States Environmental Protection Agency's limit of 11 Bq/l. The estimated total annual effective dose due to uranium and radon ranged from 3.47 to 18.84 µSv/y, with an average of 7.54 µSv/y, which is significantly lower than the European Commission's recommended limit of 100 µSv/y. This investigation represents the first study of uranium and radon levels in groundwater in the Province of Safi, providing valuable data for future research and public health.